2020
DOI: 10.3329/ralf.v7i1.46836
|View full text |Cite
|
Sign up to set email alerts
|

Pulse oximetry and clinical changes during electrosurgery in dogs anaesthetized with Xylazine-Thiopentone and Xylazine-Ketamine combinations

Abstract: This study was performed to explore the pulse oximetric evaluation of cardio-respiratory systems along with the determination of body temperature in dogs anaesthetized with xylazine-thiopentone (X-T) and xylazine-ketamine (X-K) combinations during electrosurgery. Six apparently healthy dogs weighed 20 to 25 kg undergoing electrosurgery (bipolar), were divided into two groups: group A (X-T) and group B (X-K). In group A (n=3), dogs were anaesthetized with xylazine @ 1.1 mg/kg body weight (BW) as intramuscular (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…The marginal decreased in the value of SpO 2 during anaesthesia might be attributed to the effect of xylazine which reduced the depth of respiration, but not the rate, leading to lowered oxygen saturation values [34] or it might be due to the anaesthetic agent's effects on the ventilator function of the lungs. Low SpO 2 indicates a decreased in peripheral oxygenation and tissue perfusion [25]. The observations related to the SpO 2 in this study are in accordance with [18,24,27].…”
Section: Clinico-physiological Parameterssupporting
confidence: 91%
See 1 more Smart Citation
“…The marginal decreased in the value of SpO 2 during anaesthesia might be attributed to the effect of xylazine which reduced the depth of respiration, but not the rate, leading to lowered oxygen saturation values [34] or it might be due to the anaesthetic agent's effects on the ventilator function of the lungs. Low SpO 2 indicates a decreased in peripheral oxygenation and tissue perfusion [25]. The observations related to the SpO 2 in this study are in accordance with [18,24,27].…”
Section: Clinico-physiological Parameterssupporting
confidence: 91%
“…Clinico Rectal Temperature was decreased significantly (p < 0.01) at 30 min, 45 min and during recovery from anaesthesia in both the groups when compared to base value (0 min). The decreased in rectal temperature might be attributed to depression of thermoregulatory centre in the hypothalamus [6,24,25] or due to muscle relaxation, decreased in metabolic rate and thermoregulatory centre depression as a sequel of anaesthesia [26,27]. The observations regarding rectal temperature are comparable with the observations reported by [6,[24][25][26][27][28].…”
Section: Clinico-physiological Parameterssupporting
confidence: 69%
“…However, a study conducted by Shekarfourosh et al reported that infarct size was reduced by 0.1% in ketamine/xylazine compared to other groups using tetrazolium chloride staining ( Shekarforoush et al, 2016 ), a high dose of ketamine (200 mg/kg) - xylazine (60 mg/kg) has been shown to protect the isolated guinea-pig heart from the ischemic-reperfusion injury ( Sloan et al, 2011 ). The combination of ketamine/xylazine or ketamine/diazepam has antiarrhythmic properties in ischemic/reperfusion animal models; even arrhythmias were less than pentobarbital or thiopental sodium ( Munif et al, 2020 ). An in vivo study by Zornik et al (2010) was performed to investigate the effect of three anesthetics, thiopental sodium, pentobarbital, and urethane, on ischemic ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…In combination with ketamine, it could effectively lessen ketamine side effects such as muscle stiffness. Several studies showed that alpha-receptors' activation of the sympathetic nervous system before an ischemic condition had reduced ischemic ventricular arrhythmias ( Gonca, 2015 ; Shekarforoush et al, 2016 ; Munif et al, 2020 ). Based on these findings, it can be concluded that using the combination of ketamine/xylazine has a preconditioning effect to decrease ischemic ventricular arrhythmias ( Svorc et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%